2021
DOI: 10.20473/spmrj.v3i1.21550
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Muscles Activity during Punches in Virtual Reality Exergame on Standing and Sitting Position

Abstract: Background: Physical activity (PA) provides various health benefits. Unfortunately, individuals with disabilities may experience health problems and greater obstacles to PA participation. Boxing exergame (EXG) based on virtual reality (VR) can be an alternative option to increase physical activity level because it is fun, relatively affordable and accessible. Punching in boxing requires complex movements, wherein the lower limbs are contributor for effective punches. An understanding of muscles activity is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The results showed that even with the same exercise, different muscle groups were activated to varying degrees, indicating the importance of focusing on specific muscle group activation for muscle training. Compared to traditional strength training, there has been relatively little research on exergaming, but Putra et al [ 12 ] investigated the activation levels of upper limb muscles during a punching game while in standing and sitting positions. The results showed significant differences in the activation of the upper trapezius muscle during the execution of an uppercut punch, but not for straight or hook punches, indicating that the fixedness of the movements also affects the activation levels of different muscle groups in exergaming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that even with the same exercise, different muscle groups were activated to varying degrees, indicating the importance of focusing on specific muscle group activation for muscle training. Compared to traditional strength training, there has been relatively little research on exergaming, but Putra et al [ 12 ] investigated the activation levels of upper limb muscles during a punching game while in standing and sitting positions. The results showed significant differences in the activation of the upper trapezius muscle during the execution of an uppercut punch, but not for straight or hook punches, indicating that the fixedness of the movements also affects the activation levels of different muscle groups in exergaming.…”
Section: Discussionmentioning
confidence: 99%
“…This may allow individuals to activate and recruit more muscle fibers, leading to increased muscle activation compared to more traditional exercises such as push-ups. Additionally, the Ring-Con provides a unique form of resistance that can be adjusted to individual fitness levels, potentially allowing for greater customization and variety in workout routines [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies (Lockwood & Tant, 1997;Shigeki et al, 2018) assessed EMG of muscles involved in boxing-related punching techniques, none investigated the upper body muscle EMG while performing different jab techniques. However, a study was conducted by Putra et al (2021) investigated the EMG of upper body muscles while performing jab in standing and sitting variations indicated no significant differences. Since the study was confined to execution of jab in sitting variations and only on adults, it limits the implication of their results to young boxers.…”
Section: Introductionmentioning
confidence: 98%
“…Such information may help to design better training drills and physical fitness test batteries (Oliva-Lozano & Muyor, 2020;Türker & Sözen, 2013). Putra et al (2021), used surface EMG on dominant upper limb muscles of healthy male adult (31.9 ± 3.1 years) during punch performance (in a virtual reality environment) in standing and sitting positions, revealing no difference in the percentage of maximum EMG of upper trapezius, anterior deltoid, biceps and triceps muscles of dominant side. Shigeki et al (2018) examined the three-dimensional trunk kinematics and surface EMG of lower back muscle activity among experienced and inexperienced male boxers (20.9 ± 1.6 years) during a straight punch with the dominant and non-dominant arms and noted greater EMG in the inexperienced group.…”
Section: Introductionmentioning
confidence: 99%